The Beatryce Prophecy - DiCamillo, Kate; Blackall, Sophie (Somerville, Massachusetts : Candlewick Press, 2021)
"We shall all, in the end, be led to where we belong. We shall all, in the end, find our way home. In a time of war, a mysterious child appears at the monastery of the Order of the Chronicles of Sorrowing. Gentle Brother Edik finds the girl, Beatryce, curled in a stall, wracked with fever, coated in dirt and blood, and holding fast to the ear of Answelica the goat. As the monk nurses Beatryce to health, he uncovers her dangerous secret, one that imperils them all-for the king of the land seeks just such a girl, and Brother Edik, who penned the prophecy himself, knows why. And so it is that a girl with a head full of stories-powerful tales-within-the-tale of queens and kings, mermaids and wolves-ventures into a dark wood in search of the castle of one who wishes her dead. But Beatryce knows that, should she lose her way, those who love her-a wild-eyed monk, a man who had once been king, a boy with a terrible sword, and a goat with a head as hard as stone-will never give up searching for her, and to know this is to know everything. With its timeless themes, unforgettable cast, and magical medieval setting, Kate DiCamillo's lyrical tale, paired with resonant black-and-white illustrations by Caldecott Medalist Sophie Blackall, is a true collaboration between masters"--
Keywords: Magic -- Juvenile fiction; Orphans -- Juvenile fiction; Storytelling -- Juvenile fiction; Monasteries -- Juvenile fiction; Prophecies -- Juvenile fiction; Secrets -- Juvenile fiction; Middle Ages -- Juvenile fiction; Fate and fatalism -- Fiction; Prophecies -- Fiction; Kings, queens, rulers, etc. -- Fiction; Storytelling -- Fiction; Fantasy fiction